2013
DOI: 10.2106/jbjs.l.01030
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Radiographic Femoroacetabular Impingement Morphology in Adolescents and Young Adults: An EOS-Based Double-Cohort Study

Abstract: There was a high prevalence of radiographic impingement morphology beyond the spectrum of normal in this double-cohort study of adolescents. Femoroacetabular impingement remains a dynamic problem, and we caution against relying only on the use of hard-set static radiographic parameters when evaluating femoroacetabular impingement. This study raises the important question of what morphologic characteristics should be defined as abnormal, when at least one finding of impingement morphology is noted in such a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
0
23
2
1
Order By: Relevance
“…An abnormal AP a-angle was noted in 5.6% of males and 6.7% of females, and was significantly more common in the adolescents without scoliosis. 8 Carsen and colleagues reported cam morphology exclusively in adolescents with closed physes. None of the subjects in their prephyseal closure group had elevated a-angles on MRI, whereas 14% of their closed physeal group had elevated a-angles and all were male.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An abnormal AP a-angle was noted in 5.6% of males and 6.7% of females, and was significantly more common in the adolescents without scoliosis. 8 Carsen and colleagues reported cam morphology exclusively in adolescents with closed physes. None of the subjects in their prephyseal closure group had elevated a-angles on MRI, whereas 14% of their closed physeal group had elevated a-angles and all were male.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Few studies have examined the prevalence of FAI morphology in the asymptomatic pediatric population. [7][8][9] While some studies reported cam morphology in children as young as 10 years and pincer morphology in children as early as 12 years of age, 7 other studies demonstrated cam morphology exclusively in adolescents with closed physes. 9 The pathogenesis of FAI is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic necrosis mechanically weakens the femoral head and subsequent mechanical loading contributes to the femoral head deformity 4 and ultimately alteration in growth of the femoral bone 3,5 . Acetabular changes similar to development dysplasia often accompany femoral remodeling 3,6 . In some cases, secondary arthritis ensues regardless of management 3,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Care should be taken in interpreting these images, however, because in one recent study of adolescents without hip problems, 93% of hip radiographs showed at least one parameter suggestive of impingement. 12 Therefore, in the absence of hip pain, such findings are not necessarily pathologic. For patients with hip symptoms and radiographic findings of impingement, a magnetic resonance arthrogram should be obtained to assess associated injuries to the labrum or articular cartilage.…”
Section: Introductionmentioning
confidence: 99%